Biomonitoring of Human Impacts in Freshwater Ecosystems: The Good, the Bad and the Ugly - Friberg, Nikolai; Bonada, Núria; Bradley, David C; Dunbar, Michael J; Edwards, Francois K; Grey, Jonathan; Hayes, Richard B; Hildrew, Alan G; Lamouroux, Nicolas; Trimmer, Mark; Woodward, Guy (Advances in ecological research, 2011)
It is critical that the impacts of environmental stressors on natural systems are detected, monitored and assessed accurately in order to legislate effectively and to protect and restore ecosystems. Biomonitoring underpins much of modern resource management, especially in fresh waters, and has received significant sums of money and research effort during its development. Despite this, the incorporation of science has not been effective and the management tools developed are sometimes inappropriate and poorly designed. Much biomonitoring has developed largely in isolation from general ecological theory, despite the fact that many of its fundamental principles ultimately stem from basic concepts, such as niche theory, the habitat template and the r-K continuum. Consequently, biomonitoring has not kept pace with scientific advances, which has compromised its ability to deal with emerging environmental stressors such as climate change and habitat degradation. A reconnection with its ecological roots and the incorporation of robust statistical frameworks are key to progress and meeting future challenges. The vast amount of information already collected represents a potentially valuable, and largely untapped, resource that could be used more effectively in protecting ecosystems and in advancing general ecology. Biomonitoring programmes have often accumulated valuable long-term data series, which could be useful outside the scope of the original aims. However, it is timely to assess critically existing biomonitoring approaches to help ensure future programmes operate within a sound scientific framework and cost-effectively. Investing a small proportion of available budgets to review effectiveness would pay considerable dividends. Increasing activity has been stimulated by new legislation that carries the threat of penalties for non-compliance with environmental targets, as is proposed, for example, in the EU's Water Framework Directive. If biomonitoring produces poor-quality data and has a weak scientific basis, it may lead either to unjustified burdens placed on the users of water resources, or to undetected environmental damage. We present some examples of good practice and suggest new ways to strengthen the scientific rigour that underpins biomonitoring programmes, as well as highlighting potentially rewarding new approaches and technologies that could complement existing methods. [PUBLICATION ABSTRACT]